Application of Design Thinking in the Development of the Beres.in Application: an Integrated Solution for Moving and Home Cleaning Services - Ainiyya Hana Pathi Seruni; Yulia Suryadi; Gindu Siswo (Green Publisher Indonesia, 2026)
The increase in mobility of urban residents, especially in Bogor City, has created a new need for moving and home cleaning services that are efficient, transparent, and easily accessible digitally. Changes in the lifestyle of urban communities that demand convenience and practicality encourage the need for integrated solutions that address the challenges of time efficiency and trust in service providers. This research aims to develop the concept and design of the